Eficácia do dexrazoxano na prevenção de cardiotoxicidade em pacientes com câncer de mama expostos à quimioterapia com antraciclina, associado ou não ao trastuzumabe: revisão sistemática e metanálise - Ariane Vieira Scarlatelli Macedo (2018)
Background: Anthracyclines continue to rank among the most effective agents in breast cancer (BC) treatment, but its use is limited by a dose-dependent cardiotoxicity. Clinical studies have suggested that dexrazoxane could reduce this toxicity, however it is unclear whether the effect is maintained during an adjuvant treatment followed by trastuzumab. Dexrazoxane is frequently used in the metastatic setting, when higher anthracycline cumulative doses are needed, but is often omitted in adjuvancy. We aimed to analyse whether dexrazoxane is cardioprotective in all BC stages in patients receiving anthracycline-based chemotherapy followed or not by trastuzumab. Methods: We performed a systematic review and meta-analysis. The review was registreded in PROSPERO database (CRD42017077462). We searched data from 1990 to August 2017 in Cochrane Central Register of Controlled Trials, Google Scholar, MEDLINE/Pubmed, LILACS, Web of Science, articles references and ASCO proceedings. Studies assessing congestive heart failure or cardiac event (cardiac function alterations without cardiac symptoms or hospitalization for cardiac reasons) as primary endpoints were included. Secondary outcomes were potential adverse effects of dexrazoxane on oncologic response (complete or partial, overall and progression free survivals). Two reviewers independently performed the studies selection, risk of bias assessment and data extraction. Meta-analysis was done using random effect model for estimation of treatment effect. Heterogeneity was assessed by visual inspection of forest plots and by Q test. Results: Nine studies were identified, including 1545 patients. Dexrazoxane reduced heart failure incidence (RR 0.182, CI 95%: 0.080-0.413, p < 0.0001) and cardiac events (RR 0.262, CI 95%:0.169-0.407, p < 0.0001) without impact on response rate or survival. In a subgroup analysis of studies using trastuzumab after anthracycline, the overall benefit and safety of dexrazoxane was maintained. Conclusions: dexrazoxane delayed and reduced anthracycline induced cardiac toxicity, with or without trastuzumab. Its use did not interfere with the anthracycline antitumoral efficacy. These findings may have significant implications for clinical practice.